RELASI ANTAR KELEMBAGAAN DESA DALAM PEMBANGUNAN INSFRATRUKTUR DI DESA MAYANG PONGKAI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR TAHUN 2016 - Ravi Santoso; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In the administration of village governance, in Indonesia it is often experienced problems that arise related to the relationship. As well as coordination between village head and village institution in Mayang Pongkai village Kampar Kiri district Kampar regency. So far the coordination between the village head and the Village Institution is well established but there are some issues that are problematic in the coordination between the village head and the Village Institution in the village such as the problems that have occurred in Mayang Pongkai village. Where the Village Institution has little active role in carrying out its duties and functions, the Village Institution is only an approved institution. Never even supervise the village apparatus, this leads to the inconsistency between the Village Institution and the Village Head.Problems related to the synchronous partnership system established between the village head and the Village Institution in order to establish a good and prosperous working relationship it is necessary to find the right relationship partnership model for it in this study conducted in-depth research in the village of Mayang Pongkai Kampat Kiri Kampar Kiri regency.Development in the village mayang pongkai still far behind in the appeal of villages in the middle campar district. Development planning made by the village government apparatus has not been able to answer the aspirations of the community and not synergize with the vision of the village mission.The purpose of this research is to know the relation of existing village institution in Mayang Pongkai Village in construction of insfratuktur in the village.The concept of theory that researchers use is Relation and development This research uses a qualitative approach with descriptive method. In data collection, researchers used interview techniques, documentation and observation.The result of this research is the relation of village institution in Mayang Pongkai village has not run well, it is influenced by several things such as lack of membership, lack of participation of society and especially bad relationship between institutions in Mayang Pongkai Village.Keywords: relation, village institution